2007
DOI: 10.1073/pnas.0700818104
|View full text |Cite
|
Sign up to set email alerts
|

Learning-related coordination of striatal and hippocampal theta rhythms during acquisition of a procedural maze task

Abstract: The striatum and hippocampus are conventionally viewed as complementary learning and memory systems, with the hippocampus specialized for fact-based episodic memory and the striatum for procedural learning and memory. Here we directly tested whether these two systems exhibit independent or coordinated activity patterns during procedural learning. We trained rats on a conditional T-maze task requiring navigational and cue-based associative learning. We recorded local field potential (LFP) activity with tetrodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
182
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 217 publications
(202 citation statements)
references
References 43 publications
14
182
5
Order By: Relevance
“…A relation between behavioral learning and patterns of striatalhippocampal theta coherence has been suggested because high levels of cross-structure theta coherence were found in rats that learned the T-maze task used here but not in rats that failed to learn the task (14). In our analysis, we found clear examples of correlations between the phase-amplitude modulation and learning scores (Fig.…”
Section: Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…A relation between behavioral learning and patterns of striatalhippocampal theta coherence has been suggested because high levels of cross-structure theta coherence were found in rats that learned the T-maze task used here but not in rats that failed to learn the task (14). In our analysis, we found clear examples of correlations between the phase-amplitude modulation and learning scores (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…The presence of phase-amplitude coupling during the midrun period suggested that the coupling might be related to the presence of heightened coherence between the striatal and the hippocampal rhythms, which also tends to occur during this epoch (14). As shown in Fig.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations